Political Dynamics in the Selection of Judges of the Constitutional Court of Indonesia: A Critical Analysis of Integrity and Independence - Achmad Taufan Soedirjo; Faisal Santiago (Riviera Publishing, 2024)
This study aims to examine the influence of political dynamics on the selection process of Constitutional Court (MK) judges in Indonesia and its implications for the integrity and independence of the institution. The research method used is the normative juridical method with reference to Law No. 24/2003 on the Constitutional Court as amended by Law No. 7/2020. Analysis was conducted on relevant regulations and legal documents through literature studies and interviews with legal experts. The results show that in the selection of Constitutional Court judges, political factors often dominate over the principle of meritocracy, which threatens the principle of constitutional justice and reduces public trust in the Constitutional Court. The findings highlight the urgent need for transparency and accountability in the selection process of judges to strengthen the integrity and independence of the Constitutional Court. A transparent selection process will allow the public to understand and assess the process, while accountability will ensure that the selection of judges is based on objective criteria. The implication of this research is the need to strengthen public oversight mechanisms to maintain the Constitutional Court as a guardian of the constitution with integrity and independence. These measures are also expected to strengthen public trust and constitutional justice in Indonesia.